Clinical profile and outcome of Neurosurgical Patients Admitted to Intensive Care Unit of Rural Tertiary Care Center of Nepal - Giri, Praveen Kumar; Panta, Prem Prasad; Khadka, Nilam (Journal of Karnali Academy of Health Sciences, 2020)
Background: Intensive Care Unit (ICU) is a department of a hospital for patients with the most severe and life‐ threatening conditions which requires constant and close monitoring, support from specialist, equipment and medications to maintain normal physiological functions. This study will provide information about the clinical profile and outcome of the neurosurgical patient admitted in our ICU. Methods: This is a hospital based secondary data analysis carried out in the teaching hospital of KAHS, Jumla, Nepal. This study was conducted between March to June 2020. Data were retrieved from ICU record book and which had included diagnosis on admission, reason for admission, duration of admission, medical/surgical specialty requesting admission, nature of interventions, outcome of patients admitted and demographic characteristics.. The data were entered into Microsoft Excel and analyzed using SPSS 16.0. Descriptive statistics including percentage, mean, and standard deviation were calculated. Results: A total of 31 patients admitted into the ICU, where 74.2% (n=23) males and 25.8% (n=8) females giving a male to female ratio of 3:1. The ages ranged from 3 month to 70 years. The age group of 15-59 years accounted for highest 51.6% (n=16) of all the ICU admissions. Among all cases, highest 64.5% (n=20) cases were presented from Jumla. Out of the 31 admissions 77.4% (n=24) was due to head injury, while other neurosurgical cases (Stroke, spinal cord injury) accounted 22.6% (n=7). Further dividing head injuries, highest 38.7% (n=12) is due to severe head injury, 22.6% (n=7) moderate head injury and 16.1% (n=5) were mild head injury. Among Stoke cases 71.4% (n=5) cases were due to hemorrhagic origin and only 28.6% (n=2) are ischemic origin. The average length of hospital stay ranged from 1 to 30 days with a mean of 6.3 ± 6.7 days. Among them 64.5% (n=20) were managed conservatively and 35.5% (n=11) underwent surgery. After ICU management 64.5% (n=20) cases were transferred to ward, 12.9% (n=4) referred to higher center, 9.7% (n=3) expired, 13% (n=4) left against medical advice. Conclusion: Head injuries are the highest number of neurosurgical admissions into the ICU with relatively high mortality. Developing a viable trauma team and well equipped neurosurgical ICU with adequately trained staff will help to improve the outcome of patients.